A Review and Criticism On Origins and Doctrine of Fascism - Mahdi Fadaei Mehrabani; Zaniar Ebrahimi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Giovanni Gentile is the most important philosopher of fascism. His influential book Origins and Doctrine of Fascism has a key role in the theoretical aspects of fascism. In other words, the significance of this book is providing a theoretical justification of fascism as an ideology. In the present article, by studying the different ideas raised by Gentile, I attempt to clarify how Gentile explains the internal logic of Italian fascism. I will try as much as possible to show how Gentile provides a theoretical support for fascism in Italy. Furthermore, the article has a critical review of this book in the last part.